The Effect of Management Accounting Systems in Influencing Environmental Uncertainty, Energy Efficiency and Environmental Performance - Alaeddin, Omar; Shawtari, Fekri Ali; Salem, Milad Abdelnabi; Altounjy, Rana (International Journal of Energy Economics and Policy, 2019)
The current investigation analyzes the role of energy efficiency and environmental uncertainty in influencing environmental performance of Malaysian small and medium enterprises. Our examination endeavors to add to existing studies in a few different ways. To begin with, we shed some light on the specific association that could exist between the utilization of management accounting system, perceived environmental uncertainty and energy efficiency. Furthermore, we look at the consequential impacts of energy efficiency and environmental uncertainty in influencing organizational environmental performance. The results of the PLS-SEM affirm that energy efficiency, perceived environmental uncertainty and environmental performance have significantly influenced by management accounting system. The results of partial least square structural equation modeling also confirm that energy efficiency have positively and significantly influenced on the enviornmental performance of the small and medium size firms in Malaysia. The results further confirm that perceived environmental uncertainty has no significant impact on environmental performance in small and medium size enterprises in Malaysia. Keywords: Management accounting system, environmental uncertainty, Malaysia. JEL Classifications: G32, E01 DOI: https://doi.org/10.32479/ijeep.8279